Akta Perhimpunan Aman 2012 (Akta 736): Analisis dari sudut Undang-undang Jenayah Islam dan Undang-undang Malaysia (Kanun: Jurnal Undang-undang Malaysia, 2013)
Incidents of violence that erupted during Bersih 3.0 on 28 April 2012 have resulted in several criticisms of the Malaysian legal system. Law enforcement in Malaysia is perceived as weak and has failed to constrain certain quarters from manipulating existing lacuna in the Peaceful Assembly Act 2012 (Act 736). Consequently, this paper aims to discuss various issues arising from the existence of this new Act. Several strengths and weaknesses as well as the application of the provisions of this act will be highlighted. The paper will then present a comparison between the implementation of this Act and that of Islamic criminal law. Finally, several recommendations for the improvement of the provisions of the existing laws are given in order to maintain peace and harmony in the country.Keywords: peaceful assembly, rights, laws in Malaysia